1989
DOI: 10.1017/s0952523800009846
|View full text |Cite
|
Sign up to set email alerts
|

Changing distribution of GABA-like immunoreactivity in pigeon visual areas during the early posthatching period and effects of retinal removal on tectal GABAergic systems

Abstract: The distribution of GABA-like immunoreactivity in the pigeon visual system was studied during the first 9 days after hatching using a mouse monoclonal antibody, mAb 3A12, to glutaraldehyde linked GABA . GABA-like immunoreactivity was seen in cell bodies as well as in neuropil at the level of both the retina and central visual regions at any posthatching age. However, the distribution of putative GABAergic cells and processes varied with age reaching the adult pattern at around 9 days. As a general observation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…Recently GAD positivity was also found by Wang et al (2004) in the Imc neurons. The present observation supports earlier results (Dominici et al 1988;Bagnoli et al 1989; Tö mbo¨l and Ne´meth 1999) but do not completely agree with the earlier physiological observations (Wang and Frost 1991;Wang et al 1995aWang et al , 1995bWang et al , 2000Wu et al 1994). In a recent study (Wang 2003), dichotomous modulation of the receptive field of tectal neurons was reported in pigeon.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Recently GAD positivity was also found by Wang et al (2004) in the Imc neurons. The present observation supports earlier results (Dominici et al 1988;Bagnoli et al 1989; Tö mbo¨l and Ne´meth 1999) but do not completely agree with the earlier physiological observations (Wang and Frost 1991;Wang et al 1995aWang et al , 1995bWang et al , 2000Wu et al 1994). In a recent study (Wang 2003), dichotomous modulation of the receptive field of tectal neurons was reported in pigeon.…”
Section: Discussionsupporting
confidence: 56%
“…These experiments found inhibition initiated from the parvocellular nucleus (Ipc), and excitation from the magnocellular nucleus (Imc). Imunocytochemistry revealed that neurons of the Imc nucleus were GABA-positive and the neurons of the Ipc nucleus were GABA-negative (Domenici et al 1988;Bagnoli et al 1989;Tö mbo¨l et al 1995;Tö mbo¨l and Ne´meth 1998). Bagnoli et al (1989) suggested a delayed inhibition in their experiment on isthmic nuclei.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies show that these different projections particularly affect the ventral part of the DLLv. Other light microscopic studies, using immunocytochemical techniques, have revealed the presence within the DLL of fibers immunoreactive to serotonin (Gü ntü rkü n and Challet et al, 1996), different enzymes of synthesis of catecholamines (Gü ntü rkü n and Reiner et al, 1994), ChAT (Gü ntü rkü n and Medina and Reiner, 1994), GABA (Domenici et al, 1988;Bagnoli et al, 1989;Granda and Crossland, 1989; Gü ntü rkü n and Veeman and Reiner, 1994), neuropeptide Y, and l-enkephalin (Gü ntü rkü n and . The origin of these projections is still unknown.…”
Section: Fig 2 Abmentioning
confidence: 99%
“…On the other hand, data concerning the distribution of interneurons within the DLA of the pigeon are somewhat fragmentary (Domenici et al, 1988;Bagnoli et al, 1989; Gü ntü rkü n and Veeman and Reiner, 1994). We therefore sought to augment these observations with some quantitative data, particularly with reference to the DLLv, a region in which electron microscopic observations were also made (see below).…”
Section: Light Microscopymentioning
confidence: 99%